THE PREPARATION AND LIQUID CRYSTALLINE PROPERTIESOF SOME HOMOLOGUES SERIES OF 1, 2, 4-OXADIAZOLEDERIVATIVES - Jber, Nasreen; Flaieh, Zainab (Iraqi Journal of Science, 2024)
Homologues series of some derivatives of 3, 5-(4-substituted phenyl)-l, 2, 4-oxadiazole were synthesized and their phase behavior was studied. Introduction ofthe pentagonal hetero aromatic ring leads to significant changes in mesomorphicbehavior. The synthesized compounds exhibit nematic phase.